The modern state and its enemies : democracy, nationalism and antisemitism - Salzborn, Samuel 1977- (Anthem Press, 2020)
'The Modern State and Its Enemies' considers the historical intellectual developments that provided the fundaments of the modern state, informed the key theoretical questions arising in the democratic context (e.g., representation, participation, policing and the use of force), and shaped the relationship between (state) sovereignty and (individual) liberty. The modern state as a nation-state is thus based on the relationship between its territory, its people and its sovereign authority. As a result, nationalism and minorities policy are issues that are key to the state's self-conception. But historically, these have also been repeatedly used as weapons against the state, manifesting in separatism, irredentism and antidemocratic agitation. Both antisemitism and right-wing extremism have historically stood in opposition to the democratic state and continue to do so today. Antisemitism in particular is antithetical to modernity as it fundamentally rejects equality and individual liberty. This book presents its arguments in theoretical, historical and sociological terms, with a particular focus on examples from the German context. --